Coordination chemistry of a modular N,C-chelating oxazole-carbene ligand and its applications in hydrosilylation catalysis: dedicated to Professor Hansgeorg Schnöckel on the occasion of his 65th birthday - Poyatos, Macarena; Maisse-François, Aline; Bellemin-Laponnaz, Stéphane; Gade, Lutz H. (Organometallics, 2006)
Reaction of 1-mesitylimidazole with 2-chlorobenzoxazole gave the 2-benzoxazolyl imidazolium salt bzoxcarbH+Cl- (1), which was converted to the silver N-heterocyclic carbene complex [AgI(bzoxcarb)Cl] (2) by reaction with Ag2O in dichloromethane. The crystal structure analysis confirmed the monomeric nature of complex 2. The silver complex 2 was reacted with [PdCl2(COD)] to yield the corresponding palladium complex [PdCl2(bzoxcarb)] (3), for which an X-ray diffraction study established a distorted square planar configuration with the imidazolyl and the oxazolyl ring lying within the molecular plane. Upon direct reaction of the imidazolium salt 1 with Pd(OAc)2/NaI, a bis-carbene palladium complex [PdI2(bzoxcarb)2] (4) was obtained. The rhodium complex [RhCl(bzoxcarb)(CO)] (5) was prepared in high yield in a one-step reaction of 1 with [Rh(acac)(CO)2] (acac = acetylacetonate). The silver N-heterocyclic carbene complex 2 was also used as carbene transfer reagent in the synthesis of the platinum complex [PtCl2(bzoxcarb)] (6), which was found to be an active catalyst for the hydrosilylation of alkenes and alkynes.
Published online 4 April 2006
Gesehen am 13.12.2022
Keywords: Festschrift